DIFFERENCE IN OUTPATIENT’S EXPECTATION AND PERCEPTION TOWARD PHARMACY SERVICE OF RSUP DR. SARDJITO YOGYAKARTA AND RUMAH SAKIT BETHESDA YOGYAKARTA. - Ni Putu Udayana Antari; Achmad Purnomo; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pharmacy unit should always strive to satisfy patient by giving excellent pharmacy services so that thepatient become loyal and at the same time hospital’s income increases. Patient’s expectation toward governmenthospital’s services should differ with private hospital’s service. Research is carried out with ServQual method (Parasuraman et al, 1985) through the distribution of expectation and perception questionnaire to self paid outpatient or the family members in RSUP Dr. Sardjito and Rumah SakitBethesda. Patient’s satisfaction is seen from the gap or the ServQual score. Positive score shows respondent is verysatisfied, zero score shows respondent is satisfied, and negative score shows respondent is not satisfied. Difference inpatient’s expectation is analyzed using Kruskal-Wallis test and Mann Whitney test.ServQual score shows negative value for RSUP Dr. Sardjito and Rumah Sakit Bethesda in all dimensions of thetotal score for each of the dimensions. If expectation pattern at each hospital is compared, patient’s expectation inRSUP Dr. Sardjito is highest of assurance dimension and reliability, second at tangible and responsiveness dimension, and third (the lowest) a empathy dimension. Patient expectation of Rumah Sakit Bethesda is highest at assurance dimension, the other four dimensions (tangible, empathy, reliability, and responsiveness) is at the same level afterassurance. Total patient’s expectation of RSUP Dr. Sardjito and Rumah Sakit Bethesda is not difference significantly.Patient’s expectation for each dimension shows difference at empathy and reliability dimension. Key Word : patient’s satisfaction, patient expectation, RSUP Dr. Sardjito, Rumah Sakit Bethesda